Sequential batch contactors for removal of chromium (VI) from wastewater using sheep's wool - Ray, Priyasha (2017)
A Master of Science thesis in Chemical Engineering by Priyasha Ray entitled, "Sequential batch contactors for removal of chromium (VI) from wastewater using sheep's wool," submitted in May 2017. Thesis advisor is Dr. Taleb Hassan Ibrahim and thesis co-advisor is Dr. Mustafa Khamis. Soft and hard copy available.